2019
DOI: 10.32360/acmar.v52i1.33379
|View full text |Cite
|
Sign up to set email alerts
|

Rendimento E Distribuição De Pescarias De Arrasto De Fundo Para Peixes Diversos Na Costa Norte Do Brasil.

Abstract: A pescaria de arrasto de fundo para peixes diversos dispõe de considerável importância na costa norte do Brasil, apresentando grande diversidade de espécies capturadas, com ampla notoriedade para a família Scianidae. Entre essas espécies, destaca-se a pescada-gó (Macrodon ancylodon), responsável por 64% de toda biomassa capturada dessa modalidade de pescaria, assim caracterizada como a espécie-alvo. Setenta e sete vírgula quatro por cento da produção capturada é aproveitada, enquanto 22,6% dela é rejeitada, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…The specimen was morphologically identified based on the following diagnostic characters proposed by Stehmann et al (1978), indicated in the original description (Werner, 1904) State; see Figure 1). This area comprises estuaries, other sandy or muddy bottoms, and reef environments located on the coastlines of the Brazilian States of Pará (Barthem, 1985;Camargo & Isaac, 2001;Freitas et al, 2019b;Pinheiro & Frédou, 2004;Rodrigues-Filho et al, 2020;Santo et al, 2005;Silva et al, 2016), Maranhão (Almeida et al, 2011;Aragão et al, 2019;Guimarães-Costa et al, 2019;Lessa, 1986;Martins-Juras et al, 1987;Nunes et al, 2005Nunes et al, , 2011Rocha & Rosa, 2001;Silva et al, 2018), Piauí (Aragão et al, 2019;Guimarães-Costa et al, 2019;Mai et al, 2012;Melo et al, 2016) and…”
Section: Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…The specimen was morphologically identified based on the following diagnostic characters proposed by Stehmann et al (1978), indicated in the original description (Werner, 1904) State; see Figure 1). This area comprises estuaries, other sandy or muddy bottoms, and reef environments located on the coastlines of the Brazilian States of Pará (Barthem, 1985;Camargo & Isaac, 2001;Freitas et al, 2019b;Pinheiro & Frédou, 2004;Rodrigues-Filho et al, 2020;Santo et al, 2005;Silva et al, 2016), Maranhão (Almeida et al, 2011;Aragão et al, 2019;Guimarães-Costa et al, 2019;Lessa, 1986;Martins-Juras et al, 1987;Nunes et al, 2005Nunes et al, , 2011Rocha & Rosa, 2001;Silva et al, 2018), Piauí (Aragão et al, 2019;Guimarães-Costa et al, 2019;Mai et al, 2012;Melo et al, 2016) and…”
Section: Fishmentioning
confidence: 99%
“…Contrasting to species that are relatively abundant in fishery captures ( e.g ., Hypanus guttatus and H. americanus ), S. schmardae was not recorded in several studies conducted in the area between the previous southernmost confirmed records (Pará State) and the one reported in the present study (easternmost Ceará State; see Figure 1). This area comprises estuaries, other sandy or muddy bottoms, and reef environments located on the coastlines of the Brazilian States of Pará (Barthem, 1985; Camargo & Isaac, 2001; Freitas et al ., 2019b; Pinheiro & Frédou, 2004; Rodrigues‐Filho et al ., 2020; Santo et al ., 2005; Silva et al ., 2016), Maranhão (Almeida et al ., 2011; Aragão et al ., 2019; Guimarães‐Costa et al ., 2019; Lessa, 1986; Martins‐Juras et al ., 1987; Nunes et al ., 2005, 2011; Rocha & Rosa, 2001; Silva et al ., 2018), Piauí (Aragão et al ., 2019; Guimarães‐Costa et al ., 2019; Mai et al ., 2012; Melo et al ., 2016) and Ceará (Araújo et al ., 2000; Basílio et al ., 2008; Freitas et al ., 2019a; Freitas & Lotufo, 2015). This indicates how uncommon or rare this species is in this region.…”
Section: Figurementioning
confidence: 99%
“…Com base no exposto, fez-se necessário a realização de pesquisa com base em dados disponíveis na literatura, no intuito de agregar dados científico e demais informações sobre captura da C. virescens, bem como propor novas pesquisas, tendo em vista que a captura e o desembarque desta espécie, ocorrem durante todo o ano na costa norte, seja pela ação da pesca artesanal ou industrial (CHAO et al, 2015;MAIA et al, 2016;DUARTE-PAULA, 2018;FREITAS et al, 2019;.…”
unclassified